The misused of antibiotics in upper respiratory tract infections (URTI) - Sabri, Muhammad Luqman; Mohd Fathi, Siti Safiyyah; Syed Nabawi, Syarifah Nabilah (2013)
Upper respiratory tract infection (URTI) has been a common health problem among individuals in the community and primary care clinics (PCC). However, majority episodes of URTI are caused by virus but only 10% of it is due to bacteria. Therefore, antimicrobials have no benefits in the treatment of viral URTI. According to Ministry of Health National Medicines Use Survey (NMUS) conducted in 2008 at 82 government clinics, 27.8% of antibiotics were prescribed in URTI cases. Un-judicious use of antibiotics exposes patients to the risk of antibiotics overuse, unnecessary side effects, cost-stress on health budget and health insurance and more importantly, the development of bacterial-resistance. Started from October to December 2012, 500 prescriptions samples had been collected on patients diagnosed with URTI and 189(37.8%) sheets contained antibiotics. The samples were further analysed to determine the patterns of antibiotics use in the management of URTI. The result showed that from 189 prescriptions with antibiotics, 26.46% were falsely-prescribed to the patient. About 14.29% used broad-spectrum antibiotics as the first-line agent while 12.17% antibiotics were prescribed to the non-specific URTI- a viral in nature. This was totally against the National Antibiotic Guidelines (NAG) and National Institute for Health and Clinical Excellence (NICE) guidelines. Thus the information gathered in this study will act as a reference to promote a more prudent, responsible and sustainable uses of antibiotics in the treatment of URTI in Malaysia.